The Implementation of Spiritual Rehabilitation Programs at Pangkalpinang Class IIA Correctional Institution - Therie Munadi; Muhamad Adystia Sunggara (Journal of Law, Politic and Humanities, 2025)
This study investigates the implementation and challenges of spiritual guidance programs within the Pangkalpinang Class IIA Correctional Institution, as outlined in Law Number 22 of 2022 on Penitentiaries. Using a mixed juridical and empirical approach, including interviews and observations, the research analyzes various aspects of spiritual guidance, identifies prevailing challenges, and proposes strategies to improve program effectiveness. The findings reveal significant efforts in providing religious facilities and spiritual guidance, yet challenges persist, such as low inmate participation and a shortage of specialized personnel in spiritual guidance. To address these issues, collaboration with the Ministry of Religious Affairs of the Bangka Belitung Islands Province is proposed to enhance program quality. The study concludes that fostering inter-institutional cooperation is crucial to ensuring the fulfillment of inmates' religious rights and facilitating their rehabilitation and reintegration into society.